Organics transformation and energy production potential in a high rate A-stage system: a demo-scale study - Cao, Shenbin (2022)
Current high-rate activated sludge (HRAS) process is an aerobic A-stage process that would cause significant organic loss resulted from the mineralization. In this study, the feasibility of operating a high rate A-stage without aeration (HRNS) was carried out in a demo-scale plant (275 m3/h). The organics transformation and energy production potential in A-stage were explored. The developed A-stage process was demonstrated to be more effective for organics recovery compared to that operated with aeration (53.82% versus 40.94%), despite its relatively low total COD removal efficiency (54.3% versus 63.5% with aeration). Minor organics (accounted for 1.75% of incoming COD) was found to be lost in HRNS process. Moreover, sludge generated from HRNS had higher degradability and higher methane compared to that from HRAS. Overall, this study documented the feasibility of high rate A-stage without aeration, and acted as a guide in achieving energy neutrality or even energy-positive wastewater treatment.